Sleep duration and mortality in Korean adults: a population-based prospective cohort study - Sohyeon Kwon; Hyeyoung Lee; Jong-Tae Lee; Min-Jeong Shin; Sangbum Choi; Hannah Oh (BMC, 2020)
Abstract Background Increasing evidence suggests that sleep duration is associated with risks of various diseases including type 2 diabetes, cardiovascular disease (CVD), and certain types of cancer. However, the relationship with mortality is not clear, particularly in non-European populations. In this study, we investigated the association between sleep duration and mortality in a population-based prospective cohort of Korean adults. Methods This analysis included 34,264 participants (14,704 men and 19,560 women) of the Korea National Health and Nutrition Examination Survey (KNHANES) 2007-2013 who agreed to mortality follow-up through December 31, 2016. Sleep duration was self-reported at baseline and was categorized into four groups: ≤4, 5-6, 7-8, and ≥ 9 h/day. Cox proportional hazards models were performed to estimate hazard ratios (HR) and 95% confidence intervals (CI) for the associations with mortality (all-cause as well as CVD- and cancer-specific), adjusting for potential confounders. Results During up to 9.5 years of follow-up, we identified a total of 1028 deaths. We observed the lowest mortality at 5-6 h/day sleep. Compared with 7-8 h/day of sleep, short (≤4 h/day) and long (≥9 h/day) sleep were associated with a 1.05-fold (95% CI = 0.79-1.39) and 1.47-fold (95% CI = 1.15-1.87) higher all-cause mortality, respectively. After additional adjustment for self-rated health, the positive association with short sleep disappeared (HR = 0.99, 95% CI = 0.75-1.32) and the association with long sleep was slightly attenuated (HR = 1.38, 95% CI = 1.08-1.76). Long sleep was also nonsignificantly positively associated with both cancer-mortality (HR = 1.30, 95% CI = 0.86-1.98) and CVD-mortality (HR = 1.27, 95% CI = 0.73-2.21). There was no statistically significant evidence for nonlinearity in the relationships between sleep duration and mortality (all-cause as well as CVD- and cancer-specific). Effect modification by age, sex, education, and occupation were not statistically significant. Conclusions Our findings suggest that long sleep duration is associated with an increased all-cause mortality in Korean adults.